Identification of three anatomical patterns of the spinal accessory nerve in the neck by neurophysiological mapping - Lanišnik, Boštjan (Radiology and oncology (Ljubljana), 2014)
Background. In spite of preservation of the accessory nerve there is still considerable proportion of patients with partial nerve damage during modified radical neck dissection (MRND). Methods. The nerve was identified during the surgery and its branches for the trapezius muscle mapped with nerve monitor. Results. The accessory nerve was mapped during 74 hemineck dissections and three patterns were identified. In type 1 nerve exits at the posterior end of the sternocleidomastoid muscle (SCm) and then it enters the level V (66 %). In type 2 the nerve for trapezius muscle branches off before entering the SCm (22 %). In type 3 the nerve exits at the posterior part of the SCm and it joins to the cervical plexus (12 %). The nerve than exits this junction more medially as a single trapezius branch. Conclusions. The description of three anatomical patterns in level II and V could help preserving the trapezius branch during MRND.
Keywords: anatomija; anatomy; kiruško zdravljenje; možganski živci; neck dissection; nerve mapping; nevrofiziologija; shoulder disability; spinal accessory nerve